2022
DOI: 10.1002/cbin.11773
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of m6A modification in cardiovascular diseases

Abstract: Cardiovascular diseases (CVDs) contribute to the leading cause of death worldwide. Despite significant improvements in CVDs diagnosis and treatment, a continued effort to explore novel therapeutic strategies is urgently need. N6‐methyladenosine (m6A) RNA methylation, well known as the most prevalent type of RNA modifications, involved in RNA stability, nuclear exports, translation, and decoy, plays a crucial role in the pathogenesis of a variety of diseases, including CVDs, cancer, and drug resistance. Here, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
(140 reference statements)
0
10
0
Order By: Relevance
“…AAA is a degenerative disease that may lead to aortic rupture (2,5). m6A modification is the most ubiquitous mRNA modification in eukaryotes, and the role of m6A modification has been well defined in mRNA (18,21,23). Reversible m6A modification regulates a series of biological progressions, such as RNA stability, alternative splicing, and mRNA translation (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AAA is a degenerative disease that may lead to aortic rupture (2,5). m6A modification is the most ubiquitous mRNA modification in eukaryotes, and the role of m6A modification has been well defined in mRNA (18,21,23). Reversible m6A modification regulates a series of biological progressions, such as RNA stability, alternative splicing, and mRNA translation (19).…”
Section: Discussionmentioning
confidence: 99%
“…Reversible m6A modification regulates a series of biological progressions, such as RNA stability, alternative splicing, and mRNA translation (19). Abnormal expression of m6A modified protein or m6A binding protein or abnormal m6A modified level can lead to abnormal metabolism of m6A- modified related RNA and affect gene expression, which is closely related to the occurrence and development of many diseases (18,19,23,24). He et al reported a significantly high m6A level in AAA tissues compared to normal aortic tissues, and high m6A levels are correlated with a greater risk of AAA rupture (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The m 6 A could be installed by m 6 A methyltransferase complex, containing methyltransferase-like 3 (METTL3), METTL14 and Wilms tumor 1-associated protein (WTAP). Besides, m 6 A was removed by fat mass and obesity-associated protein (FTO) and alkB homologue 5 (ALKBH5) [ 22 , 23 ]. In CRC, researchers found that the m 6 A modification level increases and METTL3 level was substantially elevated in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) is the most prevalent type of internal RNA posttranscriptional modification in eukaryotic cells, and can occur in multiple types of RNA, including messenger RNA (mRNAs), ribosomal RNA (rRNAs), transfer RNA (tRNAs), long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) (3,(5)(6)(7). This modification is a reversible process (8) that is controlled by three main components: adenosine methyltransferases (writers), m6A-binding proteins (readers), and m6A demethylating enzymes (erasers) (9,10). The "writers" are m6A methyltransferases that catalyse the formation of the m6A modification (5), while the "erasers" are m6A demethylases that regulate the demethylation of the m6A modification (11,12).…”
Section: Introductionmentioning
confidence: 99%